The Effectiveness of Extensive Reading in Enhancing Students’ Reading Comprehension Ability - Sonambela, Cakra; Lambe, Livianni; Maukar, Merlin (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This research focused on The Effectiveness of Extensive Reading in Enhancing Students’ Reading Comprehension Ability on narrative text at SMP N 8 Satap Tondano. The research sample consisted of 19 students in class VIII. This study utilized a pre-experimental design consisting of a one-group pre-test and post-test design. A 20-item true/false question test was the instrument used in this study. To determine if there were any significant differences between the pre-test and post-test scores, the data were examined using a t-test and gain score. The pretest and posttest scores differed significantly, according to the data. The mean score of students’ pre-test was 54.73 and the post-test was 87.36. The ratio on the t-table was less than the value of the t-test (12,271>1,734). As a result, (H0) was turned down, and (H1) was accepted. This demonstrated that extensive reading helped students improve their reading comprehension at SMP N 8 Satap Tondano. Students also say that the extensive reading made it easier for them to focus and understood the text better. In conclusion, this study suggests that schools can use extensive reading as an alternative learning method for teaching reading, particularly reading comprehension.